Skrining Pemeriksaan Hemoglobin untuk Deteksi Dini Anemia pada Remaja Putri di SMAN 4 Baubau - Dahlia, Besse; Anwar, Rina; Alwi, Juwitriani; Ibrahim, Muh. Siddik; L. Waru, Hamsia; Fandir, Abdul (Universitas Methodist Indonesia, 2025)
Anemia is a condition in which hemoglobin (Hb), hematocrit, or erythrocyte count falls below normal. Teenage girls are at high risk of developing anemia because they have menstrual periods that cause a loss of a lot of iron in the blood. Other factors that can affect anemia are poor nutritional habits and a lack of physical activity. An attempt to reduce the incidence of anemia is to consume foods rich in iron (greens, fruits, and meats) that can increase hemoglobin levels in the blood. This activity was carried out by examining hemoglobin levels in teenage daughters for early detection of anemia and giving an assessment related to anemia. As for the results of the hemoglobin examination in the schoolgirls, of the 35 participants, there were 24 people with a hemoglobin level of <12 g/dL. With knowledge of anemia, a teenage princess is expected to be able to maintain her eating patterns, like choosing foods that are rich in iron.